Assessment of health problems and healthcare expenditure, utilization of healthcare schemes and insurances among residents of Dhanas UT Chandigarh - Thakur, Kanchan; ., Raveen; ., Sita; Kumar, Suresh; Sharma, Vineeta; Prinja, Shankar; Saini, Sushma Kumari (International Journal Of Community Medicine And Public Health, 2021)
Background: Non-communicable diseases account for high burden of morbidity and mortality all over the world. Increased burden and need of long-lasting medical care pose adverse financial implications on poor households. It becomes even more difficult in the absence of any financial risk protection (FRP). In that case the families are forced to manage health care expenditures from the money needed for their routine daily expenses thus increasing Out of pocket expenditures. Objective of the study was to assess the morbidity burden, and out of pocket (OOP) expenditure on healthcare; assess the utilization of health care insurance schemes. Methods: A cross-sectional study was conducted among the residents of Dhanas Village Chandigarh using systematic random sampling technique. Data was collected by interviewing the participants as per interview schedule on disease patterns, OOP expenditures, and coping methods used for incurring health care expenses. From total 419 selected families, one adult member from each family was interviewed at their own house setting. Results: A low insurance coverage (20.5%) was reported and among insured 66.2% had availed benefits. The illness rate was found to be 14.2% and hospitalization rate was 3.7%. The endocrinal disorders were most prevalent among the residents. One third (36.5%) of households had faced catastrophic expenditure for outpatient and 10% for the inpatient care. The salary was leading source of expenditure. Conclusions: There is low insurance coverage and high catastrophic expenditure among the households.